A Importância dos Contos de Fadas para o Desenvolvimento Psicossexual da criança: o que pensam, o que dizem e o que fazem as professoras? - Brittos, Eritânia Silmara de (2016)
This study refers to our literature and qualitative research, developed by the master's program in education at the University of West of Paraná-UNIOESTE, Campus de Francisco Beltrão-PR. We aim to meet as the teachers use the fairy tales in the Municipal early childhood Centres (CMEIs) of our municipality. We have outlined the universe of fairy tales, tracing a panorama of its origin and structure. Within that universe, the writers Charles Perrault, the Brothers Grimm and Hans Christian Andersen. We support the concepts of myths, fables and fairy tales, emphasizing the particularity of each one, emphasizing the relevance of tales in the education of young children. We used the psychoanalytic theory to discuss the importance of these stories in the psychosexual development of the child. In the empirical literature review-we do the survey of academic-scientific productions that articulated fairy tales, education, Sexual Education, sexuality and Psychoanalysis at the State universities in the State of Paraná. We located twelve (12) universities that have graduate Stricto Sensu. Select, digital collections, seventeen (17) theses and dissertations that addressed our categories of analysis. However, do not reflect exactly our search object, which is the fairy tales in the sexual education of CMEIs. In the field research we collect data in fifteen (15) and we performed CMEIs semi-structured interviews with thirty (30) teachers who work in respective CMEIs. Our purpose was to answer the following question: what are the contributions of fairy tales in sexual education in Francisco Beltrão CMEIs? Anchored in the bibliographical research and field, we identified that the teachers feel bound to perform a job based on Emancipatory sex education, with small children, from the age of fairy tales. Therefore we reaffirm the importance of initial and continuing training, with teachers, early childhood education, about sexuality. In this sense, we present some suggestions for activities that can be used as methodological support, along with the theoretical contribution to work the issues of sexuality, present in early childhood education. Our studies led us to highlight the contributions of psychoanalysis to the field of education, by presenting correlations between fairy tales and the psychosexual development of the young child. Psychoanalytic reading of Bettelheim (2014) highlights that while the fairy tale fun kids, contribute in the construction of personality, because it clarifies important points about child development. We believe that this work has allowed us to extend the look at childhood through a fundamental element for the pedagogical practice, next to small children: fairy tales. Further, the results of our research, points to the need for training in sex education for teachers who are Emancipatory in Kindergarten, in the municipality of CMEIs Francisco Beltrão-PR. This sex education, articulated the psychoanalytic knowledge as possible way of intervention with young children, through fairy tales.